This is an ongoing riddle to see how far we can get as a group.

Similar to “Just One” we try and figure out how to use six 6’s to equal 1 (O.K. that’s been solved) then 2, then 3, then 4, etc. to see how far we can get.

We are to come up with answers in sequence (2, 3, 4, 5, etc.) and the same person is not allowed to produce two answers in a row. So if I come up with the solution for 2. I must wait until someone else posts a solution for six 6’s equaling 3 before I provide a solution for six sixes equaling 7. Etc.

How high can we get 6 sixes to go?

Thank you Brent for your great submission.

We will keep this one unsolved until the great computer tells us there is no greater answer, yet 42 is the answer to everything.

66/.6 + 6/.6 – 6 = 114

66/.6 + 6 – 6/6 = 115

66/.6 + 6 +6 -6 = 116

6!/6 – (6 + 6 + 6)/6 = 117

(6-6/6)! – (6+6)/6 = 118

6!/6 – 66/66 = 119

6!/6 + 6 – 6 + 6 – 6 = 120

(66/6) x (66/6) = 121

(6 – 6/6)! + (6+6)/6 = 122

6!/6 + (6 + 6 + 6)/6 = 123

(6! + 6 + 6 + 6 + 6)/6 = 124

(6 – 6/6)! + (6 – 6/6) = 125

6!/6 + 6 + (6 – 6) x 6 = 126

(6 – 6/6)! + 6 + 6/6 = 127

6!/6 + 6 + (6+6)/6 = 128

6 + (6! + 6 + 6 + 6) / 6 = 129

6!/6 + 6/.6 + 6 – 6 = 130

66 + 66 – 6/6 = 131

6!/6 + 6 + 6 + 6 – 6 = 132

( 6 + 6 – 6/6 ) x ( 6 + 6 ) = 132

Ooops, wrong solution, how about:

66 + 66 + 6/6 = 133

(6!+6+6)/6 + 6 + 6 = 134

(6 – .6) / .6 + 6!/6 + 6 = 135

(6 – 6/6)! + 6/.6 + 6 = 136

6!/6 + 66/6 + 6 = 137

(6-6/6)!+6+6+6 = 138

(6! + 6)/6 + 6 + 6 + 6 = 139

(6! + (6+6)*6/.6)/6 = 140

(6! + 6)/6 + (6 + 6)/.6 = 141

6!/6 + 6+6+6/.6 = 142

(6 + 6) x (6 + 6) – 6/6 = 143

6!/6 +6+6+6+6=144

too easy

(6 + 6) x (6 + 6) + 6/6 = 145

(6! + 6!/6 + 6×6)/6 = 146

6 x 6 + 666/6 = 147

Let’s see if this flies… :)

asin(cos(6)) + 66 – (6+6)/6 =148

Oh man! you’re rocking it.

I had to check if it worked out (and of course it did!) but I have now idea how you came up with it, I look forward to hearing that one! Thanks for making this puzzle amazing!

Here’s what I have for 149:

(6! – 6) / 6 + 6 X 6 – 6 = 149

asin(cos(6)) + 66 + (6-6)/6 =150

(6! + 6) / 6 + 6 X 6 – 6 = 151

66/.6 + 6 + 36 =152

Ooops

66/.6 + 6 + 6*6 =152

asin(cos(6))/.6 + 6 + 6 + 6/6

asin(cos(6))/.6 + 6 + 6 + 6/6 = 153

acos(sin(6))+(6*6)/.6 + 6/.6 = 154

acos(sin(6))+(6*6 + 6.6)/.6 = 155

(6/.6 + 6/.6 + 6) * 6 = 156

asin(cos(6)) + acos(sin(6)) + 6/6 – 6 – 6 = 157

asin(cos(6)) + acos(sin(6)) – 6/.6 + 6 – 6 = 158

asin(cos(6)) + acos(sin(6)) – 6/.6 + 6/6 = 159

(6/.6 + 6) * (sqrt(6)*sqrt(6))/.6 = 160